Acute Urinary Retention Associated with an Imperforate Hymen and Hematocolpos - Aylin Aker Ayrım; Elif Gözdemir; Nilgün Öztürk Turhan; Candan İltemur Duvan; Hasan Kafalı (Medical Network, 2009)
Acute urinary retention is unusual in children and when present they are usually a candidate for visiting the emergency department upon initial diagnosis. We report a 10-year-old girl who complained of acute urinary retention depending on imperforate hymen. Ultrasonography demonstrated a large echogenic mass over the vagina and mild dilation of the uterus. Imperforate hymen associated with hematocolpos was diagnosed. Cruciate hymenotomy was performed. The symptoms resolved after the procedure. Adolescent girls who complain of urinary symptoms with no previous menstruation should have their external genitalia examined in order to rule out the possibility of imperforate hymen as the cause of acute urinary retention.